2018
DOI: 10.2135/cropsci2017.12.0736
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Term Forage and Cow–Calf Relationships for Bermudagrass Overseeded with Arrowleaf Clover or Annual Ryegrass Managed at Different Stocking Rates

Abstract: Bermudagrass [Cynodon dactylon (L.) Pers.] pastures are often overseeded with annual ryegrass (Lolium multiflorum Lam.) and/or clovers to extend grazing. The bermudagrass pastures were stocked at three levels of forage mass to quantify cow and calf average daily gain (ADG, gain ha−1) and its relationship with mass and allowance (forage dry matter/animal body weight [DM:BW]). From 2002 through 2013, ‘Coastal’ and common bermudagrass pastures were overseeded with either ‘Apache’ arrowleaf clover (Trifolium vesic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
2

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 51 publications
0
5
0
2
Order By: Relevance
“…Forage allowance tended ( P = 0.13) to be slightly greater in Yr 1 than Yr 2. These values may be compared with those reported by Rouquette et al (2018) from an 11-yr grazing experiment with bermudagrass pastures that were overseeded with annual ryegrass or arrowleaf clover to extend the warm-season grazing period. In their study, the relationship between calf ADG and ryegrass DM mass was optimized at a FA of approximately 1.3 and 1.5 kg DM/kg BW for arrowleaf clover and ryegrass, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Forage allowance tended ( P = 0.13) to be slightly greater in Yr 1 than Yr 2. These values may be compared with those reported by Rouquette et al (2018) from an 11-yr grazing experiment with bermudagrass pastures that were overseeded with annual ryegrass or arrowleaf clover to extend the warm-season grazing period. In their study, the relationship between calf ADG and ryegrass DM mass was optimized at a FA of approximately 1.3 and 1.5 kg DM/kg BW for arrowleaf clover and ryegrass, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…This time period for N fertilizer application is generally recommended to coincide shortly after spring green‐up (Keyser et al, 2019). Nitrogen fertilization rates of warm‐season perennial grasses in the region generally range from 60 to 200 kg N ha −1 applied annually, depending on standing forage production goals (Dillard et al, 2020; F. M. Rouquette, 2017; M. R. Rouquette & Smith, 2022; Santos et al, 2019; Silveira et al, 2016). The N application rate used in this study was selected to reflect either a zero‐N‐input approach or a one‐time application rate at the lower end of this range to determine forage responses and animal carrying capacity under these conditions.…”
Section: Methodsmentioning
confidence: 99%
“…Most other adapted perennial warm‐season forage systems in the region are managed under higher stocking rate strategies with moderate‐to‐high levels of fertilizer inputs to maintain pasture productivity and persistence (Hoveland, 2000). Despite these historical management practices, a changing emphasis on fertilizer input management and enhanced interest in reducing off‐farm inputs is influencing farmers’ perspectives of pasture management in warm‐season grass‐based systems (M. R. Rouquette & Smith, 2022). Forage management strategies to reduce reliance on chemical N fertilizer may include (1) incorporation of legumes to partially replace synthetic N contributions, (2) moderate to reduced fertilizer application rates, and (3) no application of fertilizer within the system (Berg, 1995; Hoveland, 2000; Muir et al, 2011; Santos et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Elevated temperatures have also been associated with increased NDF concentration (Deinum, 1966;Henderson and Robinson, 1982a;Van Soest, 1982;Da Silva et al, 1987), rapid metabolic activity (Van Soest, 1994), and reduced digestibility of warm-season perennial grasses (Deinum, 1976;Wilson and Minson, 1980;Henderson and Robinson, 1982a;Pitman and Holt, 1982;Holt and Conrad, 1986). Studies have shown that lignin (Hart et al, 1976;Woli et al, 2020) and NDF (Beaty et al, 1966;Jolliff et al, 1979;Roth et al, 1990;Marsalis, 2004;Rouquette et al, 2018;Woli et al, 2020) concentrations of bermudagrass are quadratically associated with the day of the year (DOY) during the grazing season. Both lignin and NDF concentrations increased from early spring, reached a peak around late summer, and decreased slightly thereafter until mid-fall.…”
Section: Introductionmentioning
confidence: 99%